2013
DOI: 10.1590/s1676-24442013000200004
|View full text |Cite
|
Sign up to set email alerts
|

RAGE receptor and its soluble isoforms in diabetes mellitus complications

Abstract: Chronic hyperglycemia, which is present in all types of diabetes, increases the formation of advanced glycation end-products (AGEs). The interaction of AGEs with receptor of advanced glycation end-products (RAGE) initiates a cascade of pro-inflammatory and pro-coagulant processes that result in oxidative stress, stimulating the formation and accumulation of more AGE molecules. This cyclic process, denominated metabolic memory, may explain the persistency of diabetic vascular complications in patients with sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 81 publications
1
15
0
3
Order By: Relevance
“…Plasma derived RAGE was recently considered as a possible biomarker for CN though the reported data are as yet inconclusive (Oliveira et al, 2013), and the underlying mechanisms were found to be subject to alteration of renal function (Semba et al, 2009). Recently, EVs have…”
Section: Discussionmentioning
confidence: 99%
“…Plasma derived RAGE was recently considered as a possible biomarker for CN though the reported data are as yet inconclusive (Oliveira et al, 2013), and the underlying mechanisms were found to be subject to alteration of renal function (Semba et al, 2009). Recently, EVs have…”
Section: Discussionmentioning
confidence: 99%
“…Apart its transmembrane localization, RAGE structure consist of a soluble isoform (sRAGE), formed by two processes: alternative splicing (endogenous secretory receptor for AGE (esRAGE) or proteolytic cleavage (cRAGE) mediated by disintegrins and metalloproteinases. Studies suggest that sRAGE are risk predictors for vascular complications and therapeutic targets for the prevention of DM complications 38,39 . Quantification of glycation products is routinely analyzed through the measurement of glycated hemoglobin (HbA1c), which is used to assess metabolic control in diabetic patients 8 .…”
Section: Agesmentioning
confidence: 99%
“…Microvascular complications of T1DM and T2DM appear to be related to genetic susceptibility, as there are individuals who have the disease for a long time and never developed nephropathy or retinopathy and individuals with the same glycemic control who develop microvascular complications. Also, the risk of diabetic nephropathy development increase in individuals who have relatives with T1DM with diabetic nephropathy 38,39 . Thus, genetic susceptibility may affect the development of complications.…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…NADH inibe gliceraldeído-3-fosfato-desidrogenase, aumentando as concentrações de trioses fosfato, que formam um precursor intracelular de AGEs e que leva a formação de diacilglicerol e consequente ativação da proteína cinase C (PKC), que leva a indução ou inibe a expressão de vários genes na célula (OLIVEIRA et al, 2013).…”
Section: Neuropatia Diabéticaunclassified